2008
DOI: 10.1007/s11664-008-0407-6
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Reaction in the Au-Rich Ternary Au-Pt-Sn System as a Basis for Ternary Diffusion Soldering

Abstract: Basic thermodynamic considerations indicate nonequilibrium between gold-tin intermetallic phases and platinum. Therefore, diffusion and reactions in the Au-Pt-Sn(-Ti) thin-film system have been investigated, and a mechanism of reaction is proposed based on experimental results and thermodynamic considerations. The present paper may also help researchers understand previous results that could be interpreted differently based on the new results of this work and basic thermodynamic considerations. A ternary diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…3 with significant solid solubility, a low melting filler material and no intermetallic phases occurring at the bonding temperature. No intermetallic phases are formed in the bond during the diffusion brazing process in contrast to soldering or diffusion soldering [15][16][17] which is ruled by different phase diagrams.…”
Section: Phase Diagram Applications Exemplified With Cu-nimentioning
confidence: 98%
“…3 with significant solid solubility, a low melting filler material and no intermetallic phases occurring at the bonding temperature. No intermetallic phases are formed in the bond during the diffusion brazing process in contrast to soldering or diffusion soldering [15][16][17] which is ruled by different phase diagrams.…”
Section: Phase Diagram Applications Exemplified With Cu-nimentioning
confidence: 98%
“…3(e), and results indicated that the bright phase is an Au 4 Ti phase with a small solubility of tin. There is no comprehensive description of this phase available, and as the phase is thin (∼100 nm) even after annealing, it has been difficult to evaluate this phase even with STEM and nanospot-EDS [24]. Experimental results and reasoning by Grolier and Schmid-Fetzer [24] regarding the Au4Ti phase, experimental TEM results presented by Ivey [31], and thermodynamic reasoning of binary compound formation enthalpies by Ghosh [32] all support the formation of Au4Ti with a small solubility of Sn between the (Au,Pt)Sn and Ti/Mo during the bonding process.…”
Section: A Microstructural Analysismentioning
confidence: 99%
“…Platinum has been studied as a barrier metal for eutectic Au-Sn solder, nonetheless the experimental results indicate a rapid dissolution of the Pt into the Au-Sn system [19]- [24], which raises the remelting temperature of the solder [21], [24], [25]. The increase of the remelting temperature is one of the main advantages of the SLID bonding, as it enables further high-temperature processing, such as subsequent assembly steps and getter activation (>300°C ∼15 min) of MEMS devices [4], and it also enhances the reliability at high operational temperatures.…”
Section: Introductionmentioning
confidence: 99%